Enthralling genetic regulatory mechanisms meddling insecticide resistance development in insects: role of transcriptional and post-transcriptional events - Muthu Lakshmi Bavithra, Chandramohan; Murugan, Marimuthu; Pavithran, Shanmugasundaram; Naveena, Kathirvel (Frontiers in Molecular Biosciences, 2023)
Insecticide resistance in insects severely threatens both human health and agriculture, making insecticides less compelling and valuable, leading to frequent pest management failures, rising input costs, lowering crop yields, and disastrous public health. Insecticide resistance results from multiple factors, mainly indiscriminate insecticide usage and mounted selection pressure on insect populations. Insects respond to insecticide stress at the cellular level by modest yet significant genetic propagations. Transcriptional, co-transcriptional, and post-transcriptional regulatory signals of cells in organisms regulate the intricate processes in gene expressions churning the genetic information in transcriptional units into proteins and non-coding transcripts. Upregulation of detoxification enzymes, notably cytochrome P450s (CYPs), glutathione S-transferases (GSTs), esterases [carboxyl choline esterase (CCE), carboxyl esterase (CarE)] and ATP Binding Cassettes (ABC) at the transcriptional level, modification of target sites, decreased penetration, or higher excretion of insecticides are the noted insect physiological responses. The transcriptional regulatory pathways such as AhR/ARNT, Nuclear receptors, CncC/Keap1, MAPK/CREB, and GPCR/cAMP/PKA were found to regulate the detoxification genes at the transcriptional level. Post-transcriptional changes of non-coding RNAs (ncRNAs) such as microRNAs (miRNA), long non-coding RNAs (lncRNA), and epitranscriptomics, including RNA methylation, are reported in resistant insects. Additionally, genetic modifications such as mutations in the target sites and copy number variations (CNV) are also influencing insecticide resistance. Therefore, these cellular intricacies may decrease insecticide sensitivity, altering the concentrations or activities of proteins involved in insecticide interactions or detoxification. The cellular episodes at the transcriptional and post-transcriptional levels pertinent to insecticide resistance responses in insects are extensively covered in this review. An overview of molecular mechanisms underlying these biological rhythms allows for developing alternative pest control methods to focus on insect vulnerabilities, employing reverse genetics approaches like RNA interference (RNAi) technology to silence particular resistance-related genes for sustained insect management.